Memaknai Kehidupan Setelah Kematian dalam 2 Korintus 5:1-10 dan Menurut Kebudayaan Batak Toba - Gebriel Lumban Tobing; Roselita Sinaga; Michael Juan Nababan (Jurnal Pendidikan Agama dan Teologi, 2024)
The Apostle Paul in 2 Corinthians 5 also expressed his belief regarding life after death for believers. The author can conclude that life after death is a better and happier life for those who believe. In Toba Batak society, the belief that the Tondi (spirit) of people who have experienced death is still connected with humans who are still alive in the world emphasizes that death is not the end, but rather the beginning of a meaningful spiritual journey. Traditional ceremonies and care for ancestral relics are a form of respect for life after death in Toba Batak culture. Literature study is the method used in this research.